High-temperature and high-pressure synthesis method of cubic-phase lanthanide metal trihydride
Through the high-temperature and high-pressure synthesis method based on a large cavity press, the temperature and pressure are regulated, and the stable face-centered cubic phase lanthanide metal trihydride under normal pressure is successfully prepared and intercepted, which solves the problem of unstable lanthanide metal trihydride under normal pressure, and achieves efficient hydride high-pressure phase interception.
Patent Information
- Application Number
- CN202411936460.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
The face-centered cubic phase of the lanthanide metal trihydride is only stable under high pressure, and it is difficult to maintain stability under normal pressure.
Using a high-temperature and high-pressure synthesis method based on a large cavity press, a stable face-centered cubic phase lanthanide metal trihydride under normal pressure was successfully prepared and intercepted by precisely regulating the temperature and pressure. The specific steps include using lanthanide metal dihydride powder and ammonia borane as hydrogen sources, insulating and holding pressure at 5GPa pressure and 1200-1300°C for 60 minutes, and finally unloading to normal pressure.
The preparation of a stable face-centered cubic phase lanthanide metal trihydride under normal pressure is realized, and the phenomenon of phase change into hexagonal phase is avoided, and a technical solution for intercepting high-pressure phase to normal pressure is provided.
Smart Images

Figure CN119735167A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of lanthanide metal hydrides, and particularly relates to a method for preparing lanthanide metal trihydrides under high temperature and high pressure and intercepting them to normal pressure. Background Art
[0002] Metal hydrides are a class of materials with excellent hydrogen storage properties. At the same time, these compounds also show excellent functional properties in the fields of electricity, magnetism and catalysis. In recent years, a series of major discoveries in the field of high-temperature superconductivity have also attracted much attention to this material. The development of new high-temperature and high-pressure synthesis methods for metal hydrides will help to capture high-pressure phase metal hydrides to normal pressure, which has important scientific significance and research value.
[0003] Generally, stable lanthanide metal (holmium, dysprosium, erbium, terbium, thulium, samarium, gadolinium) dihydrides under normal pressure can be hydrogenated to form hexagonal trihydrides. Under the action of pressure, the hexagonal trihydride can reversibly transform into a cubic trihydride. T.Palasyuk, M.Tkacz et al. pointed out in the article Pressure-induced structural phase transition in rare-earth trihydrides. Part I. (GdH3, HoH3, LuH3) that face-centered cubic holmium trihydride was synthesized under a high pressure of 16GPa, but when the pressure gradually decreased to normal pressure, the face-centered cubic holmium trihydride reversibly transformed into a hexagonal holmium trihydride. The high-pressure face-centered cubic phase of metal trihydrides such as dysprosium, erbium, terbium, thulium, samarium, and gadolinium transforms into a hexagonal phase at normal pressure.
[0004] The present invention adopts a high-temperature and high-pressure synthesis method based on a large-cavity press to achieve precise control of temperature and pressure. Through this high-temperature and high-pressure process, a series of high-pressure phase lanthanide metal trihydrides were successfully prepared and captured to normal pressure. Summary of the invention
[0005] The technical problem to be solved by the present invention is to break through the limitation that the face-centered cubic phase of lanthanide metal trihydride is only stable under high pressure. By precisely controlling the pressure and temperature, the face-centered cubic phase trihydride is prevented from transforming into the hexagonal phase trihydride. Thus, a face-centered cubic phase lanthanide metal trihydride that is stable under normal pressure is prepared. The present invention adopts a high-temperature and high-pressure synthesis method based on a large-cavity press to achieve this goal.
[0006] The specific technical solutions are as follows:
[0007] A high-temperature and high-pressure synthesis method of cubic phase lanthanide metal trihydride comprises the following steps: using lanthanide metal dihydride powder as a raw material, ammonia borane as a hydrogen source, wherein the molar ratio of the hydrogen source to the raw material is greater than or equal to 2, dividing the ammonia borane into two equal parts, using a tablet press to press the two parts of ammonia borane and holmium dihydride into powders, respectively, placing the formed holmium dihydride block between two pieces of ammonia borane, sequentially loading into a sample container, a heating container, a heat-insulating sealed container and a synthesis cavity, then heat-insulating and pressurizing at a pressure of 5 GPa and a temperature of 1200-1300°C for 60 minutes, cooling and depressurizing, and obtaining a face-centered cubic phase lanthanide metal trihydride stable under normal pressure.
[0008] Preferably, the molar ratio of ammonia borane to dihydride powder is 2:1.
[0009] The powder pressing molding is specifically to place the powder samples in a mold with an inner diameter of 4 mm, and press them using a tablet press in a glove box filled with argon to form a disc with a diameter of 4 mm, and the thickness of the two ammonia borane cylinders is 1 mm, and the thickness of the dihydride block is 0.5 mm.
[0010] The cooling and depressurizing means that after the power supply and heating are stopped, the assembly blocks are naturally cooled to room temperature and then depressurized to normal pressure.
[0011] Specifically, the face-centered cubic phase lanthanide metal trihydrides synthesized by the present invention include: holmium trihydride (HoH3), dysprosium trihydride (DyH3), erbium trihydride (ErH3), terbium trihydride (TbH3), thulium trihydride (TmH3), samarium trihydride (SmH3), and gadolinium trihydride (GdH3).
[0012] The 5 GPa experimental pressure condition and the 1200-1300° C. temperature condition of the present invention can be completed on a domestic SPD 6*600T six-sided top press.
[0013] Beneficial effects:
[0014] 1. The present invention uses a one-step high temperature and high pressure method, which has simple procedures, short experimental time and high efficiency.
[0015] 2. The present invention uses ammonia borane as a solid hydrogen source and does not require hydrogen gas.
[0016] 3. The present invention adopts a domestic six-sided top press to effectively stabilize the high-pressure phase of lanthanide metal trihydrides to normal pressure, providing an effective and versatile technical solution for intercepting the high-pressure phase of hydrides to normal pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the X-ray diffraction pattern of face-centered cubic holmium hydride HoH3 in Example 1.
[0018] Figure 2This is an optical micrograph of the face-centered cubic phase holmium hydride HoH3 in Example 1.
[0019] Figure 3 It is a structural diagram of face-centered cubic holmium hydride HoH3 in Example 1.
[0020] Figure 4 This is the X-ray diffraction pattern of the face-centered cubic phase dysprosium hydride DyH3 in Example 2.
[0021] Figure 5 This is an optical micrograph of the face-centered cubic phase dysprosium hydride DyH3 in Example 2.
[0022] Figure 6 This is the structural diagram of the face-centered cubic phase dysprosium hydride DyH3 in Example 2.
[0023] Figure 7 This is the X-ray diffraction pattern of face-centered cubic erbium hydride ErH3 in Example 3.
[0024] Figure 8 This is an optical micrograph of the face-centered cubic phase erbium hydride ErH3 in Example 3.
[0025] Fig. 9 This is a structural diagram of face-centered cubic erbium hydride ErH3 in Example 3.
[0026] Fig.10 This is the X-ray diffraction pattern of the face-centered cubic phase terbium hydride TbH3 in Example 4.
[0027] Fig.11 This is an optical micrograph of the face-centered cubic phase terbium hydride TbH3 in Example 4.
[0028] Fig.12 It is a structural diagram of face-centered cubic terbium hydride TbH3 in Example 4.
[0029] Fig.13 This is the X-ray diffraction pattern of the face-centered cubic phase thulium trihydride TmH3 in Example 5.
[0030] Fig.14 This is an optical micrograph of the face-centered cubic phase thulium hydride TmH3 in Example 5.
[0031] Fig.15 This is the structural diagram of the face-centered cubic phase thulium trihydride TmH3 in Example 5.
[0032] Fig.16 This is the X-ray diffraction pattern of face-centered cubic samarium hydride SmH3 in Example 6.
[0033] Fig.17 This is an optical micrograph of the face-centered cubic phase samarium hydride SmH3 in Example 6.
[0034] Fig.18 This is the structural diagram of face-centered cubic samarium hydride SmH3 in Example 6.
[0035] Fig.19 This is the X-ray diffraction pattern of face-centered cubic phase gadolinium trihydride GdH3 in Example 7.
[0036] Fig. 20 This is an optical micrograph of the face-centered cubic phase of gadolinium hydride GdH3 in Example 7.
[0037] Fig.21 This is a structural diagram of face-centered cubic gadolinium trihydride GdH3 in Example 7. DETAILED DESCRIPTION
[0038] Example 1
[0039] Commercially purchased holmium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of holmium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the holmium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed holmium dihydride block was placed between the two sheets of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the pressure at a pressure of 5 GPa and a temperature of 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase holmium trihydride block. The X-ray diffraction pattern of the sample is shown in Figure 1 As shown in the optical micrographs, Figure 2 As shown in the structure diagram Figure 3 As shown in the figure, it can be seen that the synthesized trihydride is a face-centered cubic phase and remains stable under normal pressure.
[0040] Example 2
[0041] Commercially purchased dysprosium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of dysprosium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press. The dysprosium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed dysprosium dihydride block was placed between the two pieces of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature and pressure at 5 GPa and 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase dysprosium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Figure 4 As shown in the optical micrographs, Figure 5 As shown in the structure diagram Figure 6 shown.
[0042] Example 3
[0043] Commercially purchased erbium hydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of erbium hydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the erbium hydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed erbium hydride block was placed between the two sheets of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature at 5 GPa and 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase erbium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Figure 7 As shown in the optical micrographs, Figure 8 As shown in the structure diagram Fig. 9 shown.
[0044] Example 4
[0045] Commercially purchased terbium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of terbium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the terbium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed terbium dihydride block was placed between the two pieces of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature at 5 GPa and 1300°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase terbium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Fig.10 As shown in the optical micrographs, Fig.11 As shown in the structure diagram Fig.12 shown.
[0046] Example 5
[0047] Commercially purchased thulium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of thulium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the thulium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed thulium dihydride block was placed between the two pieces of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature and pressure at 5 GPa and 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase thulium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Fig.13 As shown in the optical micrographs, Fig.14 As shown in the structure diagram Fig.15 shown.
[0048] Example 6
[0049] Commercially purchased samarium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of samarium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the samarium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed samarium dihydride block was placed between the two sheets of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature at 5 GPa and 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase samarium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Fig.16 As shown in the optical micrographs, Fig.17 As shown in the structure diagram Fig.18 shown.
[0050] Example 7
[0051] Commercially purchased gadolinium dihydride powder was used as the raw material, and ammonia borane was used as the hydrogen source. In a glove box filled with argon, 1 mmol of ammonia borane and 0.5 mmol of gadolinium dihydride were weighed. The ammonia borane was divided into two equal parts, and the two parts of ammonia borane were pressed into discs with a diameter of 4 mm and a thickness of about 1 mm using a tablet press, and the gadolinium dihydride was pressed into discs with a diameter of 4 mm and a thickness of about 0.5 mm. The formed gadolinium dihydride block was placed between the two pieces of ammonia borane, and then loaded into the sample container, heating container, heat-insulating sealed container and synthesis cavity in turn. A six-sided hydraulic press was used to keep the temperature at 5 GPa and 1200°C for 60 minutes, and finally unloaded to normal pressure to obtain a face-centered cubic phase gadolinium trihydride block. The X-ray diffraction pattern of the sample is shown in the figure. Fig.19 As shown in the optical micrographs, Fig. 20 As shown in the structure diagram Fig.21 shown.
Claims
1. A high-temperature and high-pressure synthesis method for cubic phase lanthanide metal trihydride, comprising the following steps: using lanthanide metal dihydride powder as a raw material, ammonia borane as a hydrogen source, the molar ratio of the hydrogen source to the raw material being greater than or equal to 2, dividing the ammonia borane into two equal parts, using a tablet press to press the two parts of ammonia borane and holmium dihydride into powders, respectively, placing the formed holmium dihydride block between two pieces of ammonia borane, sequentially loading into a sample container, a heating container, a heat-insulating sealed container and a synthesis cavity, then heat-insulating and pressurizing at a pressure of 5 GPa and a temperature of 1200-1300° C. for 60 minutes, cooling and depressurizing, and obtaining a face-centered cubic phase lanthanide metal trihydride that is stable under normal pressure.
2. The high temperature and high pressure synthesis method of a cubic phase lanthanide metal trihydride according to claim 1, characterized in that: The molar ratio of ammonia borane to dihydride powder is 2:
1.
3. The high temperature and high pressure synthesis method of a cubic phase lanthanide metal trihydride according to claim 1, characterized in that: The powder pressing molding is to place the powder samples in a mold with an inner diameter of 4 mm, and press them using a tablet press in a glove box filled with argon to form a disc with a diameter of 4 mm. The thickness of the two ammonia borane cylinders is 1 mm, and the thickness of the dihydride block is 0.5 mm.
4. The high temperature and high pressure synthesis method of a cubic phase lanthanide metal trihydride according to claim 1, characterized in that: The cooling and depressurizing means that after the power supply and heating are stopped, the assembly blocks are naturally cooled to room temperature and then depressurized to normal pressure.
5. The high temperature and high pressure synthesis method of a cubic phase lanthanide metal trihydride according to claim 1, characterized in that: The face-centered cubic phase lanthanide metal trihydride includes: holmium trihydride, dysprosium trihydride, erbium trihydride, terbium trihydride, thulium trihydride, samarium trihydride, and gadolinium trihydride.
Citation Information
Patent Citations
Preparation method of contact alloy for nano particle filled tungsten skeleton special structure
CN102828059A
Lanthanide metal hydride and preparation method thereof
CN116873866A
High-temperature and high-pressure preparation method of cubic-phase lutetium hydride LuH3
CN118289712A
Synthesis and hydrogen storage properties of novel metal hydrides
WO2015189417A1
Inert environment sleeve adapter
WO2024197043A2